Co-creating brand value with diaspora volunteers - Barès, Franck; Cova, Bernard (Management international / International Management / Gestiòn Internacional, 2022)
Now considered part of the international management system, diaspora networks facilitate the dissemination of home country brands abroad and market entry into foreign countries. However, the possibility of more broadly engaging members of the diaspora in co-creating home country brand value remains underexplored. Therefore, this exploratory study adopts a qualitative longitudinal approach to examine how a new brand in a developing country can benefit from the value co-creation potential of a diaspora network. The findings show how members of the diaspora act as volunteers who provide unpaid work for the brand.